2013
DOI: 10.1002/app.38836
|View full text |Cite
|
Sign up to set email alerts
|

Tangible plasticization/filler effects of sodium salts of dimer acids on the mechanical properties of styrene ionomers

Abstract: The effects of the presence of dimer acid (DA) molecules in Na-sulfonated polystyrene (PSSNa) and poly(styrene-co Na-methacrylate) (PSMANa) ionomers on the ionomer properties were investigated using a dynamic mechanical analysis technique. The DA decreased the matrix and cluster T g s of PSSNa ionomer without changing the ionic modulus, suggesting that the DA resided both in the matrix and cluster regions of PSSNa ionomer and acted mainly as a plasticizer. On the other hand, the DA decreased the cluster T g of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…The synthesis of the dimer acid using the fatty acid in vegetable oil followed previous reports [10,12,26,27]. The clay catalyzed method is well known as a better strategy to synthesize the dimer acids than radical coupling method, which inevitably leads to greater amounts of undesirable contents of trimers and higher oligomers [27].…”
Section: Synthesis Of Dimer Acidmentioning
confidence: 96%
See 3 more Smart Citations
“…The synthesis of the dimer acid using the fatty acid in vegetable oil followed previous reports [10,12,26,27]. The clay catalyzed method is well known as a better strategy to synthesize the dimer acids than radical coupling method, which inevitably leads to greater amounts of undesirable contents of trimers and higher oligomers [27].…”
Section: Synthesis Of Dimer Acidmentioning
confidence: 96%
“…It is composed of palmitic acid (C16, 15.9%), stearic acid (C18, 3.1%), oleic acid (C18, 44.9%), linoleic acid (C18, 31.5%), and some residues (4.6%) [10,12]. In this study, the fatty acids mixture consisted of 19.1% saturated fatty acid (C16) and 80.9% unsaturated fatty acids (C18) which are composed of oleic acid, linoleic acid, and their isomers [10]. The overall synthesis process is illustrated in Fig.…”
Section: Synthesis Of Dimer Acidmentioning
confidence: 99%
See 2 more Smart Citations
“…28 Relatively nonpolar dimer acid molecules were also used as plasticizers for the SPS and PSMANa ionomers. 29 It was found that an addition of the dimer acid molecules reduced both the matrix T g and cluster T g of the SPS ionomer, but as for the PSMANa ionomer it reduced only the cluster T g .…”
Section: Introductionmentioning
confidence: 96%